The Nexus Between Macroeconomics Variables And The Co2 Emissions: Empirical Evidence From Malaysian Road Transport Sector - Nur Zaimah, Ubaidillah; Rossazana, Ab. Rahim; Farhana, Ismail (The Social Sciences Research Society, 2012)
In the present paper, an attempt is made to examine the nexus between the macroeconomic variables and the CO 2 emissions from road transport sector in Malaysia. Using vector error correction model during 1980 to 2009 period, the empirical results show that there is an evidence of a long-run relationship among the variables. The findings of this research also indicate that a bi-directional relationship exist between the number of vehicles and CO 2 emission in the short- run.